Crime, Order and the Two Faces of Conservatism: an Encounter with Criminology's other. (31st March 2020) - Loader, Ian
Abstract: Over the past half century, conservatism has been a powerful force in shaping public and political responses to crime in Britain. But within criminology, conservative ideology remains curiously neglected and poorly understood. In this paper, I develop an interpretive reconstruction of conservative thinking about crime that seeks to make good this inattention. My central contention is that one finds in conservative ideology both an emotionally and culturally resonant case for making police authority and penal control central to the production of order and arguments for sceptical penal restraint and non-penal modes of socialization. But from which aspects of its conceptual morphology do these two faces of conservatism arise? In answering this question, my encounter identifies the claims that conservatism brings to contests over a better politics of crime (claims with which non-conservatives are required to reckon), as well as pinpointing certain shortcomings and blind spots of conservative ideology.